Éteres difenílicos polibromados (PBDE) como contaminantes persistentes : ocorrência, comportamento no ambiente e estratégias analíticas - Annunciação, Daniel Luiz Rodrigues da (2018)
Flame retardants are substances mixed with numerous materials to inhibit the combustion process, reducing risks and damages caused by fires. Among these substances, polybrominated diphenyl ethers (PBDEs) have been widely used for decades due to their low cost and high efficiency. However, since they are mixed and not chemically bonded to the materials, PBDEs can be released over time being transported through numerous pathways until they reach soils and aquatic systems, where they can accumulate in sediments and biota. Due to their high chemical stability, an essential feature for flame retardants, they are considered persistent contaminants. Several studies report the presence of PBDEs in atmospheric and aquatic particulate matter, sediments, soils and biological matrices such as marine animals, tissues and human fluids. In Brazil, little is known about the use and commercialization of PBDEs, as well as their levels in different environmental compartments. Thus, this review provides an overview of the origin of PBDEs in the environment as well as information inherent to the understanding of the behavior and presence of this contaminants of recent interest in different environmental compartments. Finally, the manuscript also brings state-of-the-art analytical approaches used for environmental sampling, preservation, preparation and sample analysis.